2006
DOI: 10.1208/aapsj080249
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Toxicity of Prenatal Exposure to Toluene

Abstract: Organic solvents have become ubiquitous in our environment and are essential for industry. Many women of reproductive age are increasingly exposed to solvents such as toluene in occupational settings (ie, long-term, lowconcentration exposures) or through inhalant abuse (eg, episodic, binge exposures to high concentrations). The risk for teratogenic outcome is much less with low to moderate occupational solvent exposure compared with the greater potential for adverse pregnancy outcomes, developmental delays, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
(26 reference statements)
0
10
1
Order By: Relevance
“…The results also indicate that toluene concentrates in certain compartments, including maternal liver and brain, placenta, and fetal brain, at levels substantially higher than the apparent asymptotic level in maternal blood. These very high maternal solvent exposures typical of abuse can lead to perinatal death [3], morphological teratogenicity (e.g., [7]), prematurity and/or growth restriction, microcephaly, digital and/or facial dysmorphology, and the possibility of long-term detrimental outcomes [3,49,[59][60][61]. Using this same pattern of exposure in our preclinical model, we have shown that prenatal toluene exposure delays postnatal development, restricts growth, and increases likelihood of morphological and neurobehavioral teratogenic outcome [5,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results also indicate that toluene concentrates in certain compartments, including maternal liver and brain, placenta, and fetal brain, at levels substantially higher than the apparent asymptotic level in maternal blood. These very high maternal solvent exposures typical of abuse can lead to perinatal death [3], morphological teratogenicity (e.g., [7]), prematurity and/or growth restriction, microcephaly, digital and/or facial dysmorphology, and the possibility of long-term detrimental outcomes [3,49,[59][60][61]. Using this same pattern of exposure in our preclinical model, we have shown that prenatal toluene exposure delays postnatal development, restricts growth, and increases likelihood of morphological and neurobehavioral teratogenic outcome [5,8].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, exposure to high concentrations of toluene can have numerous deleterious effects including cerebellar damage [18,19,41,42], wide-ranging neuronal atrophy, and white matter abnormalities [35,41,46,48,51,63] as well as neurological syndromes such as ataxia, myopathy, peripheral neuropathy, convulsions, and encephalopathy [17,19,29,36,42]. Children who have been exposed to toluene in utero may also suffer from deficits in later development [7,32]. Toluene is lipid soluble, freely crosses the placenta [20,60], and clinical cases of toluene-related embryopathy and malformations are evident in women who have abused toluene during their pregnancies [3,21,27,28,49,59,60].…”
Section: Introductionmentioning
confidence: 99%
“…However, the patterns of incidental exposure under these occupational circumstances (i.e., relatively constant, low-level exposures) in typically wellregulated workplaces reduce that risk. In contrast, the repeated intentional inhalation of very high concentrations of toluene in binge patterns of exposure typical of solvent abuse-exposures that rapidly yield high peak blood toluene concentrations -may present a relatively greater risk [Bowen and Hannigan 2006]. However, that remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…This current review elaborates a previous review of basic research on toluene abuse exposure during early development [Bowen and Hannigan 2006]. The prior brief review compared various animal models of prenatal toluene exposure, focusing primarily on behavioral outcomes, whereas the current, more extensive review emphasizes clinical studies, addresses a wider range of outcomes, and shows how our understanding of those outcomes is aided by the research in animal models of binge inhalation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of toluene have been investigated in younger animals, the majority of these studies have focused on gestational exposure followed by later assessment of toluene's effects in pre-weanling and older animals [see review [6]]. For example, results from our laboratory and others have shown that repeated, brief, high-concentration binge maternal toluene exposure adversely impacts prenatal development and early postnatal maturation of pups (PN22-PN63), as well as their spontaneous exploration and amphetamineinduced locomotor activity [6], [7], [22,27]. These results suggest that exposure to high concentrations of toluene during early development may be more deleterious than exposure during adulthood.…”
Section: Introductionmentioning
confidence: 99%